2017
DOI: 10.3390/cancers9080108
|View full text |Cite
|
Sign up to set email alerts
|

National and Subnational Population-Based Incidence of Cancer in Thailand: Assessing Cancers with the Highest Burdens

Abstract: In Thailand, five cancer types—breast, cervical, colorectal, liver and lung cancer—contribute to over half of the cancer burden. The magnitude of these cancers must be quantified over time to assess previous health policies and highlight future trajectories for targeted prevention efforts. We provide a comprehensive assessment of these five cancers nationally and subnationally, with trend analysis, projections, and number of cases expected for the year 2025 using cancer registry data. We found that breast (ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 73 publications
5
88
0
1
Order By: Relevance
“…This is consistent with the reported incidence in a previous study which studied the trend in incidence of five cancers and prediction of future trends in each region of Thailand. The study found that the incidence rates of other regions (north, central, south) would be continuously decreasing in the future until 2030 (Virani et al, 2017). Thus, the projection is ensured when there is no major change affecting the screening scheme in the near future if the screening is still continuing indefinitely.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is consistent with the reported incidence in a previous study which studied the trend in incidence of five cancers and prediction of future trends in each region of Thailand. The study found that the incidence rates of other regions (north, central, south) would be continuously decreasing in the future until 2030 (Virani et al, 2017). Thus, the projection is ensured when there is no major change affecting the screening scheme in the near future if the screening is still continuing indefinitely.…”
Section: Discussionmentioning
confidence: 96%
“…In the south, the APC was increasing at 2.1% per year before 2000. The drop in ASR after the year 2000 was obvious and continuous with APC of -5.0% per year (Virani et al, 2017). We have hypothesized that the decline in the incidence of cervical cancer might be the result of the organized screening program.…”
Section: Discussionmentioning
confidence: 98%
“…Since 2006, NCI has played a leading role in carrying out cancer prevention campaigns, with five does and don't using a wide variety of education materials, talks at schools, and public education through all social media al., 2016). A decrease was projected in all geographic zones except the North-East during 2012-2025 (Virani et al, 2017). However, a decreasing trend in incidence of cervical cancer in Khon Kaen was evident from 1990 to 2014 with a prediction of continuous decrease until 2029 (Saenrueang et al, 2019).…”
Section: Healthy Life-style Promotionmentioning
confidence: 92%
“…From 2000 to 2012, CRC was the only malignancy in Thailand with an increased incidence in both sexes (average annual percent changes in males = 4.1% and in females = 3.1%) regardless of geographic region [2]. Currently, CRC is the third leading cancer in males and the fourth most common cancer in females.…”
Section: Incidence and Staging Of Colorectal Cancer In Thailandmentioning
confidence: 99%